2016
DOI: 10.1093/infdis/jiw038
|View full text |Cite
|
Sign up to set email alerts
|

HLA Immunogenotype Determines Persistent Human Papillomavirus Virus Infection in HIV-Infected Patients Receiving Antiretroviral Treatment

Abstract: A proportion of human immunodeficiency virus (HIV)-infected patients develop persistent, stigmatizing human papillomavirus (HPV)-related cutaneous and genital warts and anogenital (pre)cancer. This is the first study to investigate immunogenetic variations that might account for HPV susceptibility and the largest to date to categorize the HPV types associated with cutaneous warts in HIV-positive patients. The HLA class I and II allele distribution was analyzed in 49 antiretroviral (ART)-treated HIV-positive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Although associations between HPV infection and Human Leukocyte Antigen (HLA) genotypes have previously been described 6, the relationship between HIV/HPV co-infection, class II HLA and cervical cancer development has not been reported 7. It is also unclear what the immune mechanism would be 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although associations between HPV infection and Human Leukocyte Antigen (HLA) genotypes have previously been described 6, the relationship between HIV/HPV co-infection, class II HLA and cervical cancer development has not been reported 7. It is also unclear what the immune mechanism would be 8.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of cervical cancer has been related to certain high-risk HLA class II genes 15. Polymorphisms in HLA-DRB1 and -DQB1 genes are hypothesized to play a role in carcinogenesis of cervical cancer 6. Despite considerable scientific interest, findings of different published studies have been inconsistent 10,16,17.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (13), we described an association, or likely protection from cervical cancer in HIV-1/HPV co-infected South African women, with certain HLA II genotypes. Furthermore, a study carried out by Meys et al (42) reported that specific HLA immunogenotypes can determine the persistence of HPV infection in HIV-1 infected patients even during antiretroviral treatment. The presence of HIV-1/HPV co-infection in combination with specific HLA II genotypes or a haplotype may increase or decrease the risk of cervical disease development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that, despite underlying immunodeficiency and immune reconstitution, the existing cervical carcinogenesis process in HIV/HPV co-infected women is further influenced by host molecular genetic factors, which vary between individuals (18,23,24) (Figure 1). It has also been suggested that the rate of cervical disease progression and likely protection may depend on host immunogenetic variations (25)(26)(27)(28)(29).…”
Section: Ivyspring International Publishermentioning
confidence: 99%